Continental Margin Sedimentation 2007
DOI: 10.1002/9781444304398.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Delivery to the Seabed on Continental Margins

Abstract: On river-influenced continental margins, terrigenous muds tend to accumulate in the middle of the continental shelf. The common occurrence of mid-shelf mud belts has been attributed to three basic across-margin transport mechanisms. Muds either diffuse to the mid-shelf under the influence of storms, or they are advected there by oceanographic currents, or they arrive at the mid-shelf in dense suspensions that flow across the margin under the influence of gravity. Until recently, observations generally favoured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 124 publications
(350 reference statements)
2
34
0
Order By: Relevance
“…Based on calculation of sediment flux, Goodbred (2003) estimated that two-thirds of the sediment load of the Holocene Ganges River is trapped in the delta and delta plain, and 1/3 passes down the ''Swatch of No Ground'' Canyon onto the Bengal Fan, which is known to have been active throughout the Holocene (Weber et al 1997). In the Eel River case, clay and silt is transported within the littoral cell to the head of Eel Canyon (Hill et al 2007), and turbidity currents have been observed within the canyon itself: Hill et al (2007) estimate that 50 to 80% of the clay-and silt-size sediment supplied by the Eel River during the period of measurement has been transported through Eel Canyon to the deep-water basin.…”
Section: Mud-floored Canyonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on calculation of sediment flux, Goodbred (2003) estimated that two-thirds of the sediment load of the Holocene Ganges River is trapped in the delta and delta plain, and 1/3 passes down the ''Swatch of No Ground'' Canyon onto the Bengal Fan, which is known to have been active throughout the Holocene (Weber et al 1997). In the Eel River case, clay and silt is transported within the littoral cell to the head of Eel Canyon (Hill et al 2007), and turbidity currents have been observed within the canyon itself: Hill et al (2007) estimate that 50 to 80% of the clay-and silt-size sediment supplied by the Eel River during the period of measurement has been transported through Eel Canyon to the deep-water basin.…”
Section: Mud-floored Canyonsmentioning
confidence: 99%
“…Even the mud fraction, however, tends to accumulate in shoreline-parallel bands unless it encounters a submarine canyon (e.g., Hill et al 2007).…”
Section: Fluvial-shallow Marine To Deep Water Connectionsmentioning
confidence: 99%
“…However, anthropogenic activities that have been increasing during the last century -such as tin mining on and offshore, construction of tourist resorts, deforestation, agriculture and urbanization -all cause river discharge due to increased exposure to weathering and erosion of fine-grained sediment (Wolanski and Spagnol, 2000). In the course of flash floods during the southwest monsoon (rainy season), these fine sediments are subsequently transported through ephemeral channels towards the sea (e.g., Curran et al, 2002;Mulder et al, 2003;Malmon et al, 2004;Owens, 2005;Hill et al, 2007). Enhanced sedimentation due to anthropogenic impacts has been observed in different settings such as tropical estuaries in Papua New Guinea, Vietnam, Australia and Indonesia (Wolanski and Spagnol, 2000); the Pearl River in Hong Kong (Owen and Lee, 2004;Owen, 2005); and the Waiapu River in New Zealand (Wadman and McNinch, 2008).…”
Section: Identification Of Event Depositsmentioning
confidence: 99%
“…Their deposits have to be considered while identifying offshore backflow tsunami deposits. Flash-flood deposits are typically coarsegrained (Postma, 2001) or alternating sand and mud layers (Martin, 2000), but they also comprise stratified deposits of silty clay within mud belts (Cutter and Diaz, 2000;Hill et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cacchione et al 1984Cacchione et al :1280. 263 The mechanisms responsible for these mud patches on continental shelves across the world are only beginning to be understood (Hill et al 2009;Ogston et al 2005); no research concerning this has been conducted on the inner continental shelf in Ghana. …”
mentioning
confidence: 99%